Menjembatani Kesenjangan dalam Manajemen Dislipidemia di Indonesia Melalui Strategi ACS Europath: Analisis - Richard Antonius; Akhtar Fajar Muzakkir (Cermin Dunia Kedokteran, 2025)
Dyslipidemia is a significant global public health concern, particularly in Indonesia. Current dyslipidemia guidelines stated the management should be done with a combination of lifestyle and pharmacological interventions. Treatment with lipid lowering agents should be initiated early for better prognostic benefit. ACS Europath IV project emphasizes the importance of early intensification of lipid-lowering therapy to reduce the risk of recurrent cardiovascular events and improve patient outcomes. This literature review the current state of dyslipidemia management in Indonesia and discussing the potential role of ACS Europath strategies in improving patient outcomes.